La cadena de valor del cultivo de la naranja (citrus sinensis) de la provincia de Mariscal Cáceres – Región de San Martín - Del Aguila Melendez, Gustavo (2014)
The present study on orange crop value chain (Citrus sinensis) in Province of Mariscal Caceres - Reg\on San Mart\n, cons\sted on analyzŋ the l\nks of value cha\ns, so both primary and support activities, where it has determinad that among those involved of sector exist a litt)e bit organization leve! of producers, from an interna! logistic, operations, externa! . logistic, marketing and post-sales service; also there are weaknesses pronunciated in conceming to the supplying, human resources managing, infrastructuring and tecnology developing. The study was worked at interna! and externa! environment through a workshop with producers, where the matrix was developed with Strengths, Weaknesses, Opportunities and Threats (SWOT) and wtth the Hsted; strategies were raised with development or improvements fer productiva sector of orange. Finally, it was determined the causes and sub-causes of problem of the low level of organization of producers, using as a tool of analysis the lshikawa's diagram, evaluating for components of productive sector, such as the fruit, crop, market and producers, browsing causes and sub-causes with it, and putting emphasis to the solution could perform strategic proposals worked on analysis of environment and reducing the risks and doubt of cultivation the next years.